Gender differences in land inheritance, schooling, and lifetime income: evidence from the rural Philippines - Estudillo, Jonna P.; Quisumbing, Agnes R.; Otsuka, Keijiro (Informa UK Limited, 2001)
This article examines the difference in lifetime incomes arising from parental preferences in the allocation of land inheritance and investments in schooling between sons and daughters in the rural Philippines. Sons are preferred with respect to land inheritance, receiving 0.15 additional hectares of land, while daughters are treated more favourably in schooling investments, receiving 1.5 more years of schooling. However, differences in both current and life-cycle incomes between sons and daughters are insignificant. This suggests that Filipino parents allocate intergenerational transfers to equalise incomes among their children, without sacrificing efficiency. -- Authors' Abstract